Higher Education Research Collaboration to Support Excellence and Competitiveness - Cudai Nur, Andi; Sofia Rukmana, Novayanti; Nuryamin, Muhammad; Ali Qalati, Sikandar; Ali, Wazir (Indonesian Association for Public Administration (IAPA), 2023)
This manuscript is the result of research which aims to understand the reality of LP2M UNM collaboration which is implemented in research by collaborating with universities, schools, communities, private and government institutions. The methodology used is qualitative with interview techniques, documentation and observation. Qualitative analysis approach with steps of data collection, reduction, data presentation, and drawing conclusions. The data sources are documents, observations and interviews with informants who are directly related to the implementation of the collaboration, as well as several internal and external stakeholders involved. The argument from the results of this research is that